Kesejahteraan Psikologis Pada Majelis Pengkajian Tauhid Tasawuf (MPTT) Abuya Syekh Haji Amran Waly Al-khalidi di Kabupaten Aceh Selatan: Psychological Well-being at the Tauhid Tasawuf Study Council (MPTT) of Abuya Syekh Haji Amran Waly Al-Khalidi in South Aceh Regency - Hendri (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
The Movement of the Majelis Pengkajian Tauhid Tasawuf (MPTT), led by Abuya Syekh Haji Amran Waly Al-Khalidy, has become a social phenomenon that captures the attention of the Islamic community in Indonesia, characterized by the expression of religious practices through dhikr, commonly referred to as ratep serebe. This research aims to understand the depiction of Psychological Well-being within the Majelis Pengkajian Tauhid Tasawuf (MPTT) Abuya Syekh Haji Amran Waly Al-Khalidy in Kabupaten Aceh Selatan. The study employs a descriptive quantitative approach. Data collection utilized the Psychological Well-being scale based on Ryff's theory (1995) with a reliability score of 0.893. The population in this study consists of the Majelis Pengkajian Tauhid Tasawuf (MPTT) Abuya Syekh Haji Amran Waly Al-Khalidy in Kabupaten Aceh Selatan, with a sample of 60 individuals with use of cluster sampling technique. The research findings indicate that the Psychological Well-Being of the Majelis Pengkajian Tauhid Tasawuf (MPTT) Abuya Syekh Haji Amran Waly Al-Khalidy in Kabupaten Aceh Selatan is, on average, categorized as high.